2004
DOI: 10.1369/jhc.4a6249.2004
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of In Situ Hybridization Signals in Rat Testes

Abstract: S U M M A R YWe performed basic research into quantifying in situ hybridization (ISH) signals in rat testis, a suitable organ for the quantification because germ cells undergo synchronized development and show stage-specific gene expression. In this model experiment, rRNA was selected as the hybridizable RNA in paraffin sections. Specimens fixed with Bouin's fixative and hybridized with digoxygenin-labeled probes could easily be analyzed quantitatively through "posterization" of the images. The amount of rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…All corrected signal intensities from the same slide were then Z-transformed to overcome the problem of their non-linearity and absence of normal distribution, which finally enabled us to compare various brain regions on each slide. It is, however, important to keep in mind that ISH signals only reflect relative changes in copy numbers and thus only allow a relative assessment of the signal intensity in each section [42]. Our study would thus not be suited to detect an absolute overall increase in mitochondrial gene transcription after birth, as described by other scientists [31][33].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…All corrected signal intensities from the same slide were then Z-transformed to overcome the problem of their non-linearity and absence of normal distribution, which finally enabled us to compare various brain regions on each slide. It is, however, important to keep in mind that ISH signals only reflect relative changes in copy numbers and thus only allow a relative assessment of the signal intensity in each section [42]. Our study would thus not be suited to detect an absolute overall increase in mitochondrial gene transcription after birth, as described by other scientists [31][33].…”
Section: Discussionmentioning
confidence: 89%
“…In contrast to mRNA array analysis, ISH signals are notoriously difficult to quantify because numerous confounding factors might interfere [42]. On the other hand, ISH offers the advantage to assess gene expression at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…We used rat testes for basic research to quantify ISH signals because spermatogenic cells in this organ undergo synchronized development and show stage-specific gene expression, allowing the differences in signal intensities among spermatogenic cell groups to be clearly demonstrated [14]. In that experimental model, we selected a well-preserved segment of rRNA [39] as the hybridizable RNA in paraffin sections and concluded that ISH rRNA staining and the posterization of the signal intensity were useful parameters for the quantitative analysis of mRNA; in other words, for the detection of the total transcriptional activity in the tissue sections.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous paper, we described several problems that had been overcome in the quantification of mRNA in tissue sections [14]. These problems were 1) whether or not there was linearity between the probe concentration and the ISH signals, 2) whether or not the number of probe molecules per unit area or per cell cross-section accurately reflected the cellular mRNA content [17], 3) that there were differences in the accessibility of the probes to mRNA among the mRNAs, 4) that the variance in the degree of fixation reflected the degree of accessibility of probes among different tissue sections [5], and 5) that proteolytic permeabilization depended on the degree of fixation and was critical [16, 33], while different cell types often had different optima for permeabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation